The magneto-mechanical response of magnetostrictive composites for stress sensing applications. (2nd May 2017) - Yoffe, Alexander; Shilo, Doron
Abstract: Stress induced magnetic field changes in epoxy-based Terfenol-D composite materials offer a unique way for stress sensing by using a remote magnetic field sensor. The article presents a study of key factors that are crucial to the performance of stress sensors but have not been studied before. These include the sensitivity, reversibility, hysteresis and strain rate effects. Measurements of magnetic hysteresis curves revealed the enormous effect of the 180° domain switching on the amplitude of the magnetic field induced by the sample. Simultaneous measurements of the stress, strain and magnetic field exhibit no recognizable residual strain, high level of reversibility and small amount of hysteresis in the magnetic field versus stress curves. Comparison between calculated and measured curves demonstrated good agreement and strengthened the model assumptions. The results of this study indicate on the suitability of magnetostrictive composites for stress sensing applications.